Changes in Circulating Cytokines and Adipokines After RYGB in Patients with and without Type 2 Diabetes. Issue 3 (23rd February 2021) - Katsogiannos, Petros; Kamble, Prasad G.; Pereira, Maria J.; Sundbom, Magnus; Carlsson, Per‐Ola; Eriksson, Jan W.; Espes, Daniel
Abstract : Objective: This study aimed to compare cytokine and adipokine levels in patients with obesity with and without type 2 diabetes (T2D) at baseline and 6 months after Roux‐en‐Y gastric bypass (RYGB) with healthy controls. Methods: A total of 34 patients (21 with T2D) with BMI of 30 to 45 kg/m 2 were compared with 25 healthy controls without obesity. Cytokines, adipokines, and peptides of relevance for inflammation and metabolism were analyzed in plasma. Results: Significant decreases in weight and glycated hemoglobin A1c were observed. At baseline, interleukin‐6 (IL‐6), IFN‐β, IL‐18, leptin, and hepatocyte growth factor were higher in all patients with obesity compared with healthy controls. In patients without T2D, TNF‐α, IL‐1α, IL‐2, IL‐15, and visfatin were also increased, whereas bone morphogenic protein‐4 was decreased. Following RYGB, IL‐6 and hepatocyte growth factor were still increased in both groups compared with controls. In T2D patients, IFN‐β, IL‐27, IL‐1α, IL‐2, regenerating islet‐derived protein 3A, visfatin, and osteopontin were found to be increased. In patients without T2D, TNF‐α, IL‐1α, IL‐2, IL‐15, leptin, and visfatin remained increased. Conclusions: The altered cytokine profile of patients with obesity persisted after RYGB despite large weight loss and improved metabolic status, thus reflecting an inherent inflammatory state.